Tumor-Associated Neutrophils Can Predict Lymph Node Metastasis in Early Gastric Cancer - Wang, Yaohui; Zhai, Jing; Zhang, Tiancheng; Han, Shutang; Zhang, Yifen; Yao, Xuequan; Shen, Lizong (Frontiers in Oncology, 2020)
The consensus of endoscopic therapy for early gastric cancer (EGC) mainly depends on its clinicopathological features. However, the roles of tumor-associated neutrophils (TANs) in EGC remain uncertain. Here, we explored its predictive role for lymph node metastasis (LNM) in EGC. Three hundred twenty-two patients who underwent radical gastrectomy for EGC were enrolled. Preoperative peripheral blood was used to analyze the neutrophil-to-lymphocyte ratio (NLR), and the different status of TANs was determined by hematoxylin & eosin staining (H&E) and immunohistochemistry (IHC). TANs, rather than NLR, were associated with tumor size, Lauren classification, lymphovascular invasion (LVI) and LNM positively. Univariate analysis revealed that TANs were associated with LNM as well as tumor size, depth of invasion, Lauren classification, histolological classification, LVI and perineural invasion. In addition to histolological classification and LVI, TANs was found to be an independent risk factor for LNM in EGC (P=0.013). Stratification analysis by depth of invaion showed LVI in SM1 tumor, both LVI and TANs (P=0.042) in SM2 tumor were independent risk factors for LNM. In conclusion, TANs in EGC can predict LNM, and TANs may help to estimate LNM precisely in addition to the current criteria.